Directional overcurrent coordination: a bilevel optimization approach (2019)
This document presents a new methodology for the optimal coordination of directional overcurrent relays (ANSI 67) in interconnected electric power systems. The objective is to find out all the relay settings (time dial settings) that minimize the overall average system relay time operation (ASROT) according a pre- specified coordination interval whatever the location of the fault or perturbation in the transmission system. The introduction of the ASROT concept is a key contribution of this work. To find the optimal ASROT the optimization problem must be stated as a bilevel approach where the upper optimization problem aims to select the relevant perturbation that accomplish global coordination constraints from a set of sub-optimization problems (the lower optimization problems) based on the seminal optimal directional relay coordination approach (ODOCR) introduced by Urdaneta, Nadira and Pérez Jiménez in 1986. The upper optimization level is solved using a Montecarlo approach and the lower optimization levels are solved using a LP approach (Maltab's linprog tool) and a Montecarlo approach. The idea was illustrated in a simple three bus system.